1) 1/ 3 ÷ 1 /9 = 1 /3 × 9/ 1 = 1·9/3·1 = 9/ 3 = 3 · 3 /3 = 3 = 3
2)3/ 8 ÷ 1 /2 = 3 /8 × 2/ 1 = 3·2 /8·1 = 6/ 8 = 3 · 2/ 4 · 2 = 3/ 4 = 0.75
3)4 /9 ÷ 8 /9 = 4 /9 × 9/ 8 = 4·9/ 9·8 = 36 /72 = 1 · 36 /2 · 36 = 1 /2 = 0.5
4)1 /12 ÷ 1/ 6 = 1/ 12 × 6/ 1 = 1·6/ 12·1 = 6 /12 = 1 · 6 /2 · 6 = 1 /2 = 0.5
5)3 /5 ÷ 1 /25 = 3 /5 × 25/ 1 = 3·25/ 5·1 = 75/ 5 = 15 · 5/ 5 = 15
6)2 /7 ÷ 3 /7 = 2 /7 × 7 /3 = 2·7 /7·3 = 14/ 21 = 2 · 7 /3 · 7 = 2 /3
7)1 /10 ÷ 1 /10 = 1 /10 × 10/ 1 = 1·10/ 10·1 = 10/ 10 = 1
8)3 /4 ÷ 5 /8 = 3 /4 × 8 /5 = 3·8 /4·5 = 24 /20 = 6 · 4/ 5 · 4 = 6/ 5 = 1·5 + 1 /5 = 1 / 1 5 = 1.2
всё)
Пошаговое объяснение:
\ begin {gather} sin \ 2x + sin \ 6x = 0 \\ 2sin \ frac {2x + 6x} {2} cos \ frac {2x-6x} {2} = 0 \\ sin \ 4x \ cos \ 2x = 0 \\ \ left [{{sin \ 4x = O} \ atop {cos \ 2x = 0}} \ right. <=> \ left [{{4x = \ pi k} \ atop {2x = \ frac {\ pi} {2} +2 \ pi n}} \ right. <=> \ left [{{x = \ frac {\ pi k} {4} \ atop {x = \ frac {\ pi} {4} + \ pi n}} \ right. => x = \ dfrac {\ pi m} {4} \\ k \ in Z, \ n \ in Z, \ m \ in Z. \ ||| Ombem: \ \ \ dfrac {\ pi m} {4}; \ \ m \ in Z. \ end {gather}% 3D
Пошаговое объяснение:
(х+2,4)÷8=2,3 (2,4+2,3)×8
х=37,4